DIALOG LINTAS IMAN: UPAYA FORUM KERUKUNAN UMAT BERAGAMA DALAM MEMBANGUN KEHIDUPAN TOLERANSI UMAT BERAGAMA - Soffi, Dewi Ariyanti (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2023)
The multi-religious reality cannot be avoided by the people of Indonesia, one of which is in the Lumajang Regency. If not treated properly, this condition will create the potential that lead to religious conflict. FKUB (Forum Kerukunan Umat Beragama) is a bridge between religion and the state in uniting a pluralistic Indonesian society to create religious spaces. Interfaith dialogue is a meeting place for the community and religious leaders, through joint discussion sessions to open people's insights regarding differences. The purpose of this research is to determine the implementation of interfaith dialogue activities that have been carried out by FKUB in building a life of religious tolerance in the Lumajang Regency. Through qualitative research methods with an ethnographic approach. Then, the authors conducted observations, interviews, and literature studies online and offline for data collection techniques. Theoretical analysis carried out in this case study uses the concept of